2009
DOI: 10.1007/s00148-008-0233-4
|View full text |Cite
|
Sign up to set email alerts
|

Household vulnerability and child labor: the effect of shocks, credit rationing, and insurance

Abstract: Child labor, Education, Credit rationing, Shocks, D1, O1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 33 publications
4
75
1
4
Order By: Relevance
“…The child contribution to household income may enable households to pay some expenses, especially for poor households having limited access to credit and little saving capacities. Previous literature highlights that the probability of a child participating to economic activities increases when a household suffers from a shock (Beegle et al, [2003], Guarcello et al, [2010]; Bohara and Vasquez, [2010]…”
Section: Using Child Labour To Cope With Climate Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The child contribution to household income may enable households to pay some expenses, especially for poor households having limited access to credit and little saving capacities. Previous literature highlights that the probability of a child participating to economic activities increases when a household suffers from a shock (Beegle et al, [2003], Guarcello et al, [2010]; Bohara and Vasquez, [2010]…”
Section: Using Child Labour To Cope With Climate Vulnerabilitymentioning
confidence: 99%
“…We aim to clarify and quantify the relationships between climate change and child labour. Numerous papers have analysed the links between shocks, household vulnerability and child labour (Grootaert et Kanbur [1995]; Guarcello et al [2010]). However, to the best of our knowledge, this is the first paper that attempts to specifically study the impacts of climate changes on the children's economic status.…”
Section: Introductionmentioning
confidence: 99%
“…A 1997 study on rural India (Jacoby and Skoufias, 2008) demonstrated that parents withdrew their children from school when facing a decline in crop income. In 2003, an analysis of Guatemalan families suggested that they adjusted the activity status of children in response to idiosyncratic shocks and natural disasters, often by leaving children in school, but requiring them additionally to take on work (Guarcello et al, 2002).…”
Section: T H E E V I D E N C E T O D At Ementioning
confidence: 99%
“…These should be targeted at newly vulnerable populations in the first instance, especially in urban areas (since rural areas produce some of their own food whereas urban areas are dependent on food purchases), and very young children. Guarcello et al (2002) stress the importance of targeting children at risk, however they note that risk is not based solely on family income/economic status, but that other vulnerability factors must be taken into account.…”
Section: Safety Netsmentioning
confidence: 99%
“…Likewise, in the case of a food price crisis, the impact of the shock depends on whether households have access to other coping mechanisms, such as insurance (Guarcello, Mealli et al 2010) and household assets (Beegle, Dehejia et al 2006). Different types of households may respond to a food crisis differently.…”
Section: Introductionmentioning
confidence: 99%